2008
DOI: 10.5254/1.3548203
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Mechanical Analysis of Filled Elastomer with 3D-Finite Element Analysis and Transmission Electron Microtomography

Abstract: Analysis of deformation of the filled elastomer in mesoscopic scale was investigated with 3-D FEM (Finite Element Analysis). Combination of 3-D TEMT (Transmission Electron Micro Tomography) and Voxel-FEM enables us to reconstruct mesoscopic scale 3-D image and calculate 3-D strain distribution. To the first approximation, the calculated stress-strain behavior shows a good agreement with the experimental results. The strain concentration over 200% can be seen between carbon black aggregates, even if the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 0 publications
4
39
1
1
Order By: Relevance
“…When the applied global strain was 0.2, the maximum local strain was found to be about 0.7, which is more than three-times the applied strain. This agrees with the three-to 13-fold strain localization observed in the experiments [398,399]. However, the current studies on damage and strain softening phenomena are mostly limited to continuum modeling [32,333,395,400,401].…”
Section: Nonlinear Viscoelasticity Viscoplasticity and Damagesupporting
confidence: 77%
See 1 more Smart Citation
“…When the applied global strain was 0.2, the maximum local strain was found to be about 0.7, which is more than three-times the applied strain. This agrees with the three-to 13-fold strain localization observed in the experiments [398,399]. However, the current studies on damage and strain softening phenomena are mostly limited to continuum modeling [32,333,395,400,401].…”
Section: Nonlinear Viscoelasticity Viscoplasticity and Damagesupporting
confidence: 77%
“…However, they are also expected to be extendable to the systematic coarse-graining models or the multiple-scale-bridging methods to investigate the viscoplastic deformation mechanisms of polymer glasses. When a pre-cracked particle-reinforced elastomer specimen with a 4 × 5 mm 2 cross-section was loaded in tension, Akutagawa et al [398] found a highly localized strain region near the crack tip in a roughly circular area with diameter 0.5 mm. They utilized 3D transmission electron microtomography to extract a digital data set and reconstructed the microstructure of filler networks, as shown in Figure 28a.…”
Section: Nonlinear Viscoelasticity Viscoplasticity and Damagementioning
confidence: 99%
“…The tear strength and tensile strength likely peak as the filler is homogeneously dispersed into synthetic rubber. 45) In contrast, the tear strength and tensile strength of natural rubber are affected by the viscoelastic properties and strain-induced crystallization of the rubber as well as the volume, interface, and cavitation effects of the filler. The strain-induced crystallization of natural rubber is promoted by the stress concentration of the filler.…”
Section: High Strengthsmentioning
confidence: 99%
“…[48][49][50][56][57][58][59][60] When the particles are electrically conductive (e.g., carbon black), electrical resistance testing is another useful method to study the structure of the percolated filler network. [61][62][63][64] With the exception of transmission electron microtomography, 65,66 it is difficult to observe differences in the three-dimensional nature of jammed particle networks using microscopy. For example, the unmodified silica-filled SBR and the compound with 3.6 phr MPTMS added have very different extents of filler networking based on G versus strain amplitude data (Figure 4), yet TEM images of these two distinct compounds are quite similar as demonstrated in Figure 6.…”
Section: Flocculation Reinforcement and Glass Transition Effects 511mentioning
confidence: 99%